Analysis of a Cylinder Size Effect on the Fluid Flow Profile Around the Cylinder with OpenFOAM - Putri, Kania Nugraha; Mahmudah, Rida SN (Lambung Mangkurat University Press, 2024)
Planning and analysis of infrastructure involving cylindrical shapes such as bridge platform pillars and offshore sea piping systems are needed to ensure user safety. This study aims to determine the effect of variations in cylinder diameter on fluid flow profiles with OpenFOAM software in laminar conditions with Reynolds numbers 60, 100, and 200. The computational domain used is a rectangle with a length of 32D and a width of 20D, where D is the cylinder diameter, which in this study is varied by D, 2D, and 4D. We placed the cylinder at a distance of 8D in the direction of the x-axis and a length of 10D in the direction of the y-axis. The simulation results show that variations in cylinder diameter affect the fluid flow profile, and the drag coefficient increases with increasing variations in cylinder diameter. In addition, variations in diameter also affect the formation of vortex structures as the Reynolds number increases.